The Effect of Co-Ligands on the Performance of Single-Molecule Magnet Behaviours in a Family of Linear Trinuclear Zn-Dy-Zn Complexes with a Compartmental Schiff Base - Aravena-Ponce, D; Aravena-Ponce, D (Royal Society of Chemistry, 2024)
We present herein magneto-structural studies of three heterometallic Zn2Dy complexes: [Zn2Dy(L)2Cl2(H2O)](ClO4)·4H2O (1), [Zn2Dy(L)2Br2(H2O)](ClO4)·4H2O (2) and [Zn2Dy(L)2(OAc)I(H2O)]I3·4H2O (3), utilizing a new Schiff base ligand, N,N’-bis(3-methoxy-5-methylsalicylidene)-1,2-diaminocyclohexane (H2L). Complexes 1 and 2 exhibit remarkable magnetic relaxation behaviour with relatively high energy barriers in zero field (Ueff: 244 K for 1 and 211 K for 2) and notable hysteresis temperatures, despite the low local geometric symmetry around the central DyIII ions. The SMM performance of these complexes is further enhanced under an applied magnetic field, with Ueff increasing to 309 K for 1 and 269 K for 2, positioning them as elite members within the Zn-Dy SMM family. These findings emphasize the substantial influence of remote modulation on ZnII beyond the first coordination sphere of DyIII ions on their dynamic magnetic relaxation properties. Ab initio studies demonstrate that the relative orientation of the phenoxo-oxygen donor atoms around the DyIII ion is critical for determining the magnetic anisotropy and relaxation dynamics in these systems. Additionally, experimental and theoretical investigations reveal that the coordination of the bridging acetate towards the hard plane, combined with significant distortion from the ideal ZnO2Dy diamond core arrangement caused by the acetate ion, results in low magnetic anisotropy in complex 3, thereby leading to field-induced SMM behaviour. Overall, this study unveils the effects of co-ligands on the SMM performance in a series of linear trinuclear Zn-Dy-Zn complexes, which exhibit low local geometric symmetry around the DyIII centres. © 2024 The Royal Society of Chemistry.